INOVASI PENDIDIKAN (SUATU STUDI KEBIJAKSANAAN PENDIDIKAN ORDE LAMA) - can dra kirana (Raudhah - Proud To Be Professional, 2020)
This study aims to determine the concept of educational policy applied during the Old Order Period from17 August 1945 until before entering the New Order period. The method in this research emphasizes the type of library research. Obtained from books related to the main problem, namely the Old Order government policy in implementing the education system in Indonesia. The technique of collecting data is through books, journals, articles and magazines and the internet related to the Indonesian education system policy during the Old Order era. Data analysis used the analysis technique proposed by Miles and Huberman with the stages of data reduction, data presentation and conclusion (verification). The results of the study show that the implementation of the implementation of Indonesian education in the old order era has been fairly good, this can be shown by the development of Islamic education in tiered Madrasas at the Ibtidaiyah & Tsanawiyah level and the establishment of the Religious Teacher Education (PGA) and the State Islamic Judge Education (PHIN) madrasah. As for the application of the Islamic education system in public schools that have been going well. Public school conditions; Low Education, Teacher Education, Vocational Education & Technical Education.